Origin of Polysaccharide Depolymerase Associated with Bacteriophage Infection - Bartell, Pasquale F. (1969)
Analyses, by construction of phage growth curves, indicated that the polysaccharide depolymerase was synthesized by Pseudomonas aeruginosa strains B and BI after infection with phage 2. The kinetics of biosynthesis of the depolymerase were found to parallel closely the rate of formation of phage-directed virions, and alterations in the experimental conditions of infection were reflected by alterations in the production of enzyme. Infection with other Pseudomonas phages, 84 and 1197, did not result in the synthesis of depolymerase. The enzyme was not detectable in uninfected cultures, and no evidence was obtained for the existence of inhibitors or activators of enzyme activity in extracts of uninfected or infected cells. The results of experiments employing chloramphenicol or an auxotorphic mutant (BI arg(−)) suggested that protein synthesis de novo was essential for production of the enzyme. Various mutants of phage 2 (pdp(1), pdp(2)), which alter the synthesis of the polysaccharide depolymerase, have been isolated. These experimental results strongly support the role of the phage genome in the synthesis of this enzyme.